Relationship between maturity in sustainable innovation and business performance - Bacinello, Edilson; Tontini, Gerson (Revista de Administração da UFSM, 2018)
Sustainable Innovation (SI) combines the creation of economic, ecological and social value, having a strong connection with the dimensions of the Triple Bottom Line (TBL) in the long-term perspective. Innovating, according to these dimensions, requires the development of new instruments, as can be verified in the models of Maturity in Sustainable Innovation (MSI), to understand the construction of a certain competence and evolution of companies in a given area. In this context, this study sought to verify the relationship between MSI and the Financial and Market Performance (FMP) of companies. The quantitative research was based on the Modeling of Structural Equations (MSE) by means of software Smart PLS. The results point out the existence of a relationship between MSI and FMP, which can be explained, in part, by strategies related to the use of resources and capacities to generate competitive advantage for companies. It was also verified that theoretical discussion about innovation with a focus on sustainability remains unfinished and that both resources and organizational capacities, compete to explain the relationship between SIs and business performance (BP).